(untitled) (Research, Society and Development, 2020)
The application of mineral agricultural gypsum in acidic soil in Araripe Plateau may favor the development of elephant grass varieties, enabling the use of biomass as an alternative source of energy. This work aimed to evaluate the development in varieties of elephant grass grown under the application of mineral agricultural gypsum, at the Gypsum Pole of Araripe. Three varieties of elephant grass (Cameroon, Gramafante and Roxo) were grown, in the presence and absence of gypsum, composing a factorial arrangement (3 x 2), with 4 replications. Two evaluations were carried out, the first at 128 days after planting (DAP), in which the length and width of leaf +3, plant height, stem diameter and tillering were evaluated. In the second, at 213 DAP, all the variables mentioned above were evaluated, with the exception of the length and width of leaf +3. The application of mineral gypsum did not influence the length and width of the leaf +3, regardless of the variety. Initially, gypsum had a beneficial effect on tillering, but in the second evaluation it had a deleterious effect. The varieties of elephant grass respond differently to the application of gypsum. The Cameroon variety showed the greatest potential for cultivation with gypsum, in Araripe Plateau, in Pernambuco.